Genome-Wide Analysis of the C2 Domain Family in Soybean and Identification of a Putative Abiotic Stress Response Gene GmC2-148 - Sun, Yue; Zhao, Juan-Ying; Li, Yi-Tong; Zhang, Pei-Gen; Wang, Shu-Ping; Guo, Jun; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Ma, You-Zhi; Fang, Zheng-Wu; Xu, Zhao-Shi (Frontiers in Plant Science, 2021)
Plant C2 domain proteins play essential biological functions in numerous plants. In this study, 180 soybean C2 domain genes were identified by screening. Phylogenetic relationship analysis revealed that C2 domain genes fell into three distinct groups with diverged gene structure and conserved functional domain. Chromosomal location analysis indicated that C2 domain genes mapped to 20 chromosomes. The transcript profiles based on RNA-seq data showed that GmC2-58, GmC2-88 and GmC2-148 had higher levels of expression under salt, drought and ABA treatments. GmC2-148, encoding a cell membrane-localized protein, had the highest level of response to various treatments according to RT-qPCR analysis. Under salt and drought stresses, the soybean plants with GmC2-148 transgenic hairy roots showed delayed leaf rolling, a higher content of proline (Pro), and lower contents of H2O2, O2− and malondialdehyde (MDA) compared to those of the empty vector (EV) plants. The results of transgenic Arabidopsis in salt and drought treatments were consistent with those in soybean treatments. In addition, the soybean plants with GmC2-148 transgenic hairy roots increased transcript levels of several abiotic stress-related marker genes, including COR47, NCDE3, NAC11, WRKY13, DREB2A, MYB84, bZIP44 and KIN1 which resulted in enhanced abiotic stress tolerance in soybean. These results indicate that C2 domain genes are involved in response to salt and drought stresses, and this study provides a genome-wide analysis of the C2 domain family in soybean.